Management system for displaced families in displacement camps - Riyadh, Yasir; Mohi Al-deen, Shayma Mustafa (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Population stability is one of the biggest problems that countries suffer from it and the most influential in terms of the uneven distribution of the population over the geographical area of the country. There are many factors that work to bring about changes in the population distribution, including economic factors for individuals, social factors, as well as security factors. Security factors during the years of the war on terror in Iraq led to the displacement of many families from their residential areas to neighbouring areas. Many humanitarian and social organizations have worked to organize the lives of families in the form of temporary housing complexes or the so-called displacement camps in safe areas until they return to their areas. There are many problems (living difficulties) that these complexes suffer from, including: how to manage and organize the affairs of large numbers of families and how to deliver aid to them as well as ensuring its arrival as quickly and without logistical problems. In this research, a new administration system has been designed that transforms the traditional system in those camps into electronic system that organizes the management of these camps’ affairs electronically, ensuring ease of communication between management personnel as well as communication with the IDPs, through the formation of a database that includes all information about the IDPs, such as Number of family members, genders, ages, etc., in addition to the methods of communication and notifications to receive dues or awareness messages via SMS messages.